MAKROFAUNA TANAH PERKEBUNAN KELAPA SAWIT (Elais guineensis Jacq) DI LAHAN GAMBUT DENGAN PEMBERIAN BAHAN ORGANIK PADA TINGGI MUKA AIR TANAH BERBEDA - Santus Hendra Jaco; Wardati '; Wawan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This researchaims to know the species amountd, total individual, calculate population density (K) and relative density (KR) soil macrofauna in oil palm plantation (Elais guineensis Jacq) in peatland by giving organic matter in water level is different.This research are conducted by observation, sampling for soil macrofauna of data is determined by purposive random sampling method, and data soil macrofauna results to analyzed statistic descriptive. The results showed that the amountd species, total individual, population density and relative density of soil macrofauna were higher in water levels of 40-50 cm. The giving organic matter in the soil water level is different in the first month, giving palm fronds and Mucunna bracteata produces the number of species, the total individual, population density, and density of the soil macrofauna relative higher than that of oil palm empty fruit bunches,while in the third month the species, the total individual, population density, and density of the soil makorfauna ralatif higher in the provision of oil palm empty fruit bunches and palm fronds.In water levels same produce the amountd species, total individual, population density, and relative density of soil macrofauna higher ground in water levels of 40-50 cm except amountd species in the third month. key words : soil macrofana, water level, organic metter